2014
DOI: 10.1111/pin.12170
|View full text |Cite
|
Sign up to set email alerts
|

Radiation pathology: From thorotrast to the future beyond radioresistance

Abstract: The effects of radiation on human health have been a major concern, especially after the Fukushima Daiichi Nuclear Power Plant (FNPP) accident. We can determine these effects only from radiological disasters. The radiological contrast medium Thorotrast is known to induce hepatic cancers decades after injection. Using archival materials from Thorotrast patients, we performed molecular pathological studies to elucidate carcinogenic mechanisms of internal radiation exposure. It is emphasized here that radiation-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 41 publications
(74 reference statements)
0
13
0
Order By: Relevance
“…Malignancy associated with Thorotrast deposition is various, including malignancy in the liver, biliary tracts, hematopoietic system, lymphoma, lung, peritoneum, bone and others [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. According to Ito and his associates [15] the hepatic tumors after Thorotrast deposition comprised cholangiocarcinoma (CCA) (44 cases, 43.1 %), angiosarcoma (AS) (39 cases, 38.3 %), hepatocellular carcinoma (HCC) (16 cases, 15.7 %), triple cancers (CCA + AS + HCC) (1 case, 1 %), and double cancers (CCA + HCC) (2 cases, 2 %).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Malignancy associated with Thorotrast deposition is various, including malignancy in the liver, biliary tracts, hematopoietic system, lymphoma, lung, peritoneum, bone and others [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. According to Ito and his associates [15] the hepatic tumors after Thorotrast deposition comprised cholangiocarcinoma (CCA) (44 cases, 43.1 %), angiosarcoma (AS) (39 cases, 38.3 %), hepatocellular carcinoma (HCC) (16 cases, 15.7 %), triple cancers (CCA + AS + HCC) (1 case, 1 %), and double cancers (CCA + HCC) (2 cases, 2 %).…”
Section: Discussionmentioning
confidence: 99%
“…Thorium dioxide suspension, trade name "Thorotrast", used to be considered an apparently innocent contrast medium that was used for angiography with adequate radiodensity and no significant acute or subacute adverse reactions at the clinical standard in the past. However, it was an alpha emitter which was deposited in the reticuloendothelial system, including the liver, spleen and lymph nodes, and it irradiated such organs for a lifelong period [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Presented here is a tragic case that may be known to radiologists of older generations, but such experiences may not have been shared by younger radiologists, since almost all victims of Thorotrast injection are now dead.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the notion that cancer cells can acquire radioresistance by low-dose fractionated radiation within a short period [8,18], we developed a radioresistance model. NPC cells were PLOS ONE role in study design, data collection and analysis, decision to publish, or preparation of the manuscript.…”
Section: Treating Npc Cells With Radiationmentioning
confidence: 99%
“…of angiosarcoma is negligible. These differences show how Thorotrast-induced liver cancer is crucial to understand the oncogenic mechanisms of persistent LDR internal radiation in humans [3]. Supported by the War Victims' Relief Bureau, former Ministry of Health and Welfare of Japan, approximately 400 Thorotrast patients underwent the postmortem pathological examination.…”
Section: Questions Frequently Askedmentioning
confidence: 99%
“…This systematic archive is valuable for elucidating the molecular mechanisms of human cancers induced by internal radiation exposure, particularly as it is composed of the world's largest number of related cases with the highest quality of radiological and pathological information [4]. The profile of cancer induction is quite different between Hibakusha and Thorotrast patients, indicating that the mechanisms underlying the carcinogenic effect of radiation vary between external and internal exposure and, therefore, have to be analyzed differently [3]. LSS revealed that the likelihood of cancer is different depending on the originating organ [5].…”
Section: Questions Frequently Askedmentioning
confidence: 99%